TRACE METAL LEVELS OF SOIL-GROWN AMARANTHS ON MUNICIPAL SOLID WASTE DRAINAGE OF WUKARI METROPOLIS - Jeyol, M’ember Catherine; Vincent, Victor (FUDMA JOURNAL OF SCIENCES, 2022)
Soil metal levels of municipal solid waste (MSW) drainage and morphological traits of Amaranthus spp growing in the natural drainage of Wukari Metropolis was investigated as an ecological monitoring data survey and food chain contamination assessment. Selected morphological traits, physico-chemical parameters and the status of selected trace metal (Cr, Cu, Ni, Pb, Zn) levels of the municipal solid waste drainage used for dry season cultivation of Amaranthus spp were determined according to standard analytical procedures. Results reveals a significant soil Pb and Cr levels in the MSW drainage arising from traffic density fallouts. A higher soil organic matter content, slightly acidic pH and CEC of MSW drainage indicate the suitability of MSW drainage for Amaranths cultivation as reveals in the selected morphological traits which agrees with the findings of other works. This reflect high microbial activity in the compositing of MSW in the drainage. Trace metal levels were below the Joint WHO/FAO Codex Alimentarius permissible limits (Pb = 2mg/kg; Cr = 1.30mg/kg; Cu = 10mg/kg; Zn = 5mg/kg) but higher for Cr and Pb revealing the close proximity of study area to high traffic density of the Katsina –Ala – Jalingo Highway. Dry season irrigation farming of vegetables should be far from high traffic density. Natural treatment of MSW and subsequent utilization of drainages or dumpsites for dry season vegetable farming is environmentally-friendly than the application of inorganic fertilizers that pollute agricultural soils, groundwater surface waters and the soil ecosystem. Keywords - Municipal Solid Waste, Drainage, Dumpsite, Trace Metals, Amaranths,